A preliminary study of wind–solar hybrid systems potential in Jammu and Kashmir. Issue 9 (28th July 2020) - Sharma, Pramod Kumar; Ahmed, Siraj; Warudkar, Vilas
ABSTRACT: This paper deals with the study of wind–solar hybrid systems in the region of Jammu and Kashmir. Due to scarcity of less renewable energy resources in the J&K region, National Institute of Wind Energy, Chennai had installed different wind monitoring stations to measure the wind data at different locations. The survey reveals that four districts (LEH, KARGIL, POONCH and REASI) are suitable for small wind–solar hybrid systems. BIDDA (REASI) and CHUSHUL (LEH) are the two sites for small wind farm development due to the highest wind speed (more than 7 m/s) and power density (more than 400 W/m 2 ) at 100 m agl.